Facies Analysis and Stratigraphic Development of the Zubair Formation in the Mesopotamian Zone, Southern Iraq - Al-Rubaye, Hani H.; Gayara, Ali D.; Hussien, Aiad A. (Iraqi Journal of Science, 2019)
The Barremain-Aptian succession represented by two types of deposits, Clasits deposits of Zubair Formation. This formation is the most significant sandstone reservoir in Iraq, Deposited in fluvio- deltaic, deltaic and marine environments during the Barremain to Early Aptian age.The area of study is located in the Mesopotamian Zone at SThe Barremain-Aptian succession represented by the Clasits deposits of Zubair Formation. This formation is the most significant sandstone reservoir in Iraq which deposited in fluvio- deltaic, deltaic and marine environments during the Barremain to Early Aptian age. The area of study is located in the Mesopotamian Zone at Southern part of Iraq which represented by five oil fields (Nasira, Luhais, Suba, Tuba and West Qurnah). The petrographic study showed that quartz mineral is the main component of the sandstone in Zubair Formation with minor percentage of feldspar and rare rock fragments to classified as quartz arenite. The formation consists of mainly interbedded sandstone, shale, siltstone and sometimes thin beds of carbonate. Shale thickness increase towards east and decrease the sandstone towards the east southern of Iraq.Zubair characterized in the lower member by mud - dominated delta front associated facies. They seem to vertically separate relatively multi-storied mode and multi-lateral changes deltaic channel sand bodies resulting in compartmentalized reservoir architecture.The presence of the delta front associated facies overlaying the unconformity surface (SB1) refers to the transgressive system tract (TST). This stage was ended by the deposition the fluvial channel facies to mark a high-stand system tract (HST). The fluctuation point between the TST and HST is represented a maximum flooding surface.The middle member of Zubair Formation is characterized by moderate to well sorted quartz arenite sandstone with appearance bands of the shale overlaying the sand body. This succession was deposied in the delta plain environment with steps of sea level rise during the transgressive stage. There are two sequences as TST in this part which end with the maximum sea level rise (MFS) to mark the upper part of the Zubair Formation. The next stage was appeared high concentrations of organic matters and pyrite mineral which indicating that the sedimentary environment has been reduced to the marshes environment during the HST. The upper part of the Zubair Formation showed a shallower environment with shale dominated rocks associated with high organic matters and pyrite. This indicates to the finning up-ward mode during highstand stage when the deposition environment changed from delta plain fluvial channel to delta front mouth bar. The sea level rise marked the end of this stage when deposition the upper part of Zubair Formation, and the beginning of deposition of shallow marine carbonate of the Shuaiba Formation as shallow carbonate marine.outhern part of Iraq which represented by five oil fields (Narira, Luhais, Suba, Tuba and West Qurnah).By studying the core and thin sections, the main component of the Zubair Formation is Sand grain size ranges from very fine to course, quartz classified as a sandstone quartzarenite represented a high maturity and reflect a good reservoir property, with minor percentage of feldspar and rare rock fragments, it consists of mainly interbedded sandstone, shale, siltstone and sometimes thin beds of carbonate. Shale thickness increase towards east and decrease the sandstone towards the east southern of Iraq.Zubair Formation has three members (Lower, Middle and Upper) in the study area. The change in thickness and lithofacies depends on well locations. These changes have shown in logs, thin sections and core descriptions. These members are represented by five lithofacies deposited in the three main deltaic environments Prodelta, Delta Front (Mouth bar and Distributaries bay deep sea) and Delta Plain (Channel Sand).The Lower member of ZubairFormation consists mainly of shale with low sandstone percentage changes in thickness from minimum value in Suba, Luhais increase toward Nasira , Tuba and West Qurnah oil fields ,this member representing Transgressive systems tracts (TST) stage as rise in sea level ending with HighStand systems tracts(HST) stage reflecting a delta front association Mouth bar and Distributaries bay deep sea) in Nasria, Suba and Luhais oil fields changes to prodelta in the lower part of lower member in Tuba and West Qurnah oil fields .